Facial emotion identification impairments in Chinese persons living with schizophrenia: A meta-analysis - Xu, Yan-Min; Deng, Fang; Zhong, Bao-Liang (Frontiers in Psychiatry, 2022)
Background: Facial emotion identification (FEI) deficits are associated with impaired social functioning in persons living with schizophrenia (PLwS), but the research on emotion-specific FEI deficits remains inconclusive. Furthermore, existing studies on FEI deficits are limited by their small sample sizes. We performed a meta-analysis of studies comparing the FEI abilities between Chinese PLwS and healthy controls in terms of the six basic facial emotions (happiness, sadness, fear, disgust, anger, and surprise), as well as contempt, calmness, and neutral facial expressions. Methods: Major Chinese- and English-language databases were searched to retrieve case-control studies that compared the FEI task performance between Chinese PLwS and healthy controls (HCs) and reported the emotion-specific correct identification scores for PLwS and HCs. The Joanna Briggs Institute Critical Appraisal Checklist for Case-control Studies (“JBI checklist”, hereafter) was used to assess the risk of bias (RoB) of the included studies. Statistical analysis was performed using the “meta” package of R 4.1.2. Results: Twenty-three studies with a total of 28 case-control cohorts and 1894 PLwS and 1267 HCs were included. The RoB scores of the included studies ranged from two to seven. PLwS had statistically significant lower FEI scores than HCs and the corresponding emotion-specific pooled standard mean differences (95% confidence intervals) were -0.69(-0.88,-0.50) for happiness, -0.88(-1.12,-0.63) for sadness, -1.44(-1.83,-1.06) for fear, -1.18(-1.60,-0.76) for disgust, -0.91(-1.24,-0.57) for anger, -1.09(-1.39,-0.78) for surprise, -0.26(-0.51,-0.01) for contempt, -0.31(-0.52,-0.09) for calmness, and -0.42(-0.65,-0.18) for neutral. In the analyses of sources of heterogeneity, drug-naïve status, clinical setting, positive and negative psychotic symptoms, and RoB were significant moderators of the magnitudes of FEI deficits. Conclusions: Chinese PLwS have significant FEI impairments in terms of recognizing the six basic facial emotions, contempt, calmness, and neutral emotions, and the magnitude of impairment varies depending on the type of emotion, clinical characteristics, and the level of RoB of the study. It is necessary to consider the characteristics of FEI deficits and the clinical moderators in the FEI deficits to develop remediation strategies targeting FEI deficits in schizophrenia.